2011
DOI: 10.1177/0333102411410612
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of olfaction in patients with migraine using an odour stick identification test

Abstract: The OSIT showed certain odours to be highly offensive to migraine patients even when they were not experiencing migraine headaches. More attention should be paid to odours that are perceived to be offensive by migraine patients, particularly those with MWA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
72
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(84 citation statements)
references
References 15 publications
9
72
1
2
Order By: Relevance
“…There were 13 comparative studies between migraine and other primary headaches or controls without headache, 2,3,5,8,13,14,[17][18][19][20]22,28,31 and 10 that evaluated only migraine patients. 4,6,7,11,15,16,24,26,29,30 As for odour-triggered headache, there were six studies detected, two comparative studies between migraine and other primary headaches, 1,3 two with migraine patients, 7,24 and two case reports. 9,12 However, there were six other studies where pathophysiological aspects of the association between odours and migraine were studied.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There were 13 comparative studies between migraine and other primary headaches or controls without headache, 2,3,5,8,13,14,[17][18][19][20]22,28,31 and 10 that evaluated only migraine patients. 4,6,7,11,15,16,24,26,29,30 As for odour-triggered headache, there were six studies detected, two comparative studies between migraine and other primary headaches, 1,3 two with migraine patients, 7,24 and two case reports. 9,12 However, there were six other studies where pathophysiological aspects of the association between odours and migraine were studied.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, we observed a severe intolerance to odours, pleasant or unpleasant, during headache attacks. 2,[4][5][6][7][8]10,11,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] However, a limited number of studies showed that odours may trigger headache attacks in some patients, particularly in migraineurs 1,3,6,7,9,24 and occasionally in cluster headache patients. 12,18 This intolerance to odours is known as osmophobia, and according to two studies that investigated osmophobia in secondary headaches, it occurred during headache attacks only in the primary headaches.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There is a significant association between odors and primary headaches, particularly to migraine with or without aura [1][2][3][4][5][6] and tension-type headache [1,[6][7][8]. The literature of its occurrence in secondary headaches is very scarce [9].…”
Section: Introductionmentioning
confidence: 99%
“…The literature of its occurrence in secondary headaches is very scarce [9]. They are triggers of headache attacks [2,10] or intolerance factor (osmophobia) [1] both during and between headache attacks (pain-free period) [1,3,11,12].…”
Section: Introductionmentioning
confidence: 99%